PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU FEAR OF MISSING OUT (FOMO) PADA SISWA KELAS VII DISMP NEGERI 2 MUARO JAMBI - Chairunnisa; Sofyan, Hendra; Niki Kusaini, Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of social media has made adolescents increasingly active in using social media in their daily lives. Excessive use of social media can trigger Fear of Missing Out (FoMO) behavior, which is the feeling of anxiety or fear of missing out on information, activities, and experiences of others shared through social media. This phenomenon is commonly found among early adolescent students who tend to have high curiosity and a need to stay connected with their social environment. This study aimed to determine the level of social media use, the level of FoMO behavior, and the influence of social media use on FoMO behavior among seventh-grade students at SMP Negeri 2 Muaro Jambi. This study employed a quantitative approach with an ex post facto research design. The research population consisted of 122 seventh-grade students, with total sampling used as the sampling technique. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability. Data analysis techniques included normality testing, linearity testing, and simple linear regression analysis using IBM SPSS Statistics. The results showed that students' social media use was in the high category at 66.64%, while FoMO behavior was in the high category at 61.15%. The simple linear regression analysis showed a significance value of 0.000 < 0.05, indicating a positive and significant influence of social media use on FoMO behavior. The coefficient of determination of 88.6% indicated that FoMO behavior was strongly influenced by social media use. Thus, the higher the social media use, the higher the FoMO behavior among seventh-grade students at SMP Negeri 2 Muaro Jambi.